Easy Steps to REPORT WRITING - Fung, Anna Wai Choo, 1956-, author 277532; Choy, Tuck Onn, 1960-, author 277525 (Singapore : Marshall Chavendish Editions, 2012)
Uses a step-by-step approach to teaching the fundamentals of report writing, including the differences between formal and informal reports, writing a good introduction, and proper grammar usage.